Impact of Intellectual Capital on the Organizational Performance of Airline Industry in Malaysia - Muhammad, Khalique; Abu Hassan, Md. Isa (IGI Global, 2015)
This chapter aims to examine the role of intellectual capital in order to enhance the organizational performance of airline industry in Malaysia. Five components of intellectual capital, namely human capital, customer capital, structural capital, technological capital, and spiritual capital, were used to investigate the role of intellectual capital in airline industry in Malaysia. A structured questionnaire was used to gather the required data from Kuala Lumpur, Sultan Ismail Johor Bharu International Airport, and Kuching International Airport. A total of 195 out of 200 useable questionnaires were collected. Multiple regression analysis was employed to test the proposed research hypotheses of this study. The findings show that two variables, namely customer capital and spiritual capital, appeared as significant contributors while the remaining three variables, human capital, structural capital, and technological capital, appeared as insignificant contributors. This is a preliminary study and it could be a milestone for further studies.